Analisis Struktur dan Unsur Intrinsik dalam Drama Tradisional Nusantara - Riska Sari Putri; Sella Marleoni; Tria Putri Andini; Wilidia Nanda Agustina; Wulan Gustina; Herlinda Herlinda (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Traditional drama of the archipelago is one of Indonesia's cultural heritages that has an important role. This study aims to explore the plot structure and intrinsic elements in several forms of traditional drama in Indonesia. The study used a descriptive qualitative approach, with content analysis methods of scripts and performance documentation as the main data sources. The findings show that the plot of traditional drama generally consists of five narrative stages, namely introduction, emergence of conflict, climax, decline of tension, and resolution. Intrinsically, these dramas present universal themes such as justice, love, sacrifice and resistance to injustice, with characters clearly divided between good and evil. The plot tends to run chronologically, supported by settings that depict the real conditions of local communities, and dialog that is packaged in the form of rhymes, poems, or local languages. Moral messages are an important element in traditional dramas that strengthen local cultural values. Based on the results of the analysis, traditional Nusantara drama is proven to have a distinctive structure and rich intrinsic content, so it deserves more attention in the field of education and cultural preservation.